Language ERPs reflect learning through prediction error propagation - Fitz, Hartmut; Chang, Franklin (Cognitive psychology, 2019)
[Display omitted] •ERPs reflect error-based learning processes that support linguistic adaptation.•Error propagation explains the P600 using the same mechanism as the N400.•Explains data from three N400, five P600, one semantic P600, and three learning related studies.•Production-based prediction error ERPs in comprehension will differ from non-ERP comprehension measures.•ERPs are biological evidence for a neural learning algorithm that propagates error. Event-related potentials (ERPs) provide a window into how the brain is processing language. Here, we propose a theory that argues that ERPs such as the N400 and P600 arise as side effects of an error-based learning mechanism that explains linguistic adaptation and language learning. We instantiated this theory in a connectionist model that can simulate data from three studies on the N400 (amplitude modulation by expectancy, contextual constraint, and sentence position), five studies on the P600 (agreement, tense, word category, subcategorization and garden-path sentences), and a study on the semantic P600 in role reversal anomalies. Since ERPs are learning signals, this account explains adaptation of ERP amplitude to within-experiment frequency manipulations and the way ERP effects are shaped by word predictability in earlier sentences. Moreover, it predicts that ERPs can change over language development. The model provides an account of the sensitivity of ERPs to expectation mismatch, the relative timing of the N400 and P600, the semantic nature of the N400, the syntactic nature of the P600, and the fact that ERPs can change with experience. This approach suggests that comprehension ERPs are related to sentence production and language acquisition mechanisms.